2017
DOI: 10.4049/immunohorizons.1700030
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 Is Required for Suppression of Type 17 Immunity during Influenza and Bacterial Superinfection

Abstract: Influenza is an annual, global health care concern. Secondary bacterial pneumonia is a severe complication associated with primary influenza virus infection, often resulting in critical morbidity and mortality. Our laboratory has identified influenza-induced suppression of anti-bacterial Type 17 immunity as a mechanism for enhanced susceptibility to bacterial super-infection. We have shown that influenza-induced type I interferon impairs Type 17 activation. STAT1 is a transcription factor involved in interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…We have previously shown that influenza-associated IFNβ attenuated host bacterial defense due to suppression of Type 17 immunity ( 13 , 14 ). Also, we recently identified that Type 17 immunity is rescued in the absence of STAT1 signaling during influenza-bacterial super-infection ( 17 ). In this study, we examined the effects of MRSA challenge on day 6 of influenza infection in WT and Stat2 − /− mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that influenza-associated IFNβ attenuated host bacterial defense due to suppression of Type 17 immunity ( 13 , 14 ). Also, we recently identified that Type 17 immunity is rescued in the absence of STAT1 signaling during influenza-bacterial super-infection ( 17 ). In this study, we examined the effects of MRSA challenge on day 6 of influenza infection in WT and Stat2 − /− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Further, we have also shown increased bacterial control in Ifnar −/− mice during super-infection, suggesting that influenza-induced type I IFN is a critical mediator of antibacterial immune suppression ( 13 ). Also, we have recently shown increased Type 17 immunity in STAT1 −/− mice during super-infection ( 17 ). Therefore, we hypothesized that STAT2 deficiency would rescue suppression of Type 17 responses during influenza infection.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Lee, et al . 19 reported that STAT1 signaling played a detrimental role in influenza infection by controlling the magnitude of type 17 immune activation. GBP1 , an interferon-inducible protein, was reported to inhibit the replication of influenza virus by contributing to the host immune response 20 .…”
Section: Discussionmentioning
confidence: 99%
“…This proposal is often based on the function of the STAT1 transcription factor that is essential for each type of IFN signaling pathway. For example, STAT1 deficiencies, similar to IFNR deficiencies, in transgenic mouse models results in a marked increase in susceptibility to viral infection (3)(4)(5)(6), including respiratory viral infection (7,8). The central role of STAT1 in antiviral defense is further highlighted by observations that viruses often selectively target STAT1 function to subvert the immune response (9).…”
mentioning
confidence: 99%